Venomous and poisonous arthropods: identification, clinical manifestations of envenomation, and treatments used in human injuries - Haddad Junior, Vidal [UNESP] (2015)
This review presents the main species of venomous and poisonous arthropods, with commentary on the clinical manifestations provoked by the toxins and therapeutic measures used to treat human envenomations. The groups of arthopods discussed include the class Arachnida (spiders and scorpions, which are responsible for many injuries reported worldwide, including Brazil); the subphylum Myriapoda, with the classes Chilopoda and Diplopoda (centipedes and millipedes); and the subphylum Hexapoda, with the class Insecta and the orders Coleoptera (beetles), Hemiptera (stink bugs, giant water bugs, and cicadas), Hymenoptera (ants, wasps, and bees), and Lepidoptera (butterflies and moths).